A contribuição de um programa de saúde da terceira idade na promoção de saúde e qualidade de vida - Coelho, Almir Resende (2012)
Nowadays, population aging is a widely discussed and researched topic all over the world. Data from the World Health Organization (WHO) shows that the population life expectancy in Americas rose from 74 years old in 2000 to 76 years old in 2008. Epidemiological studies, involving the elderly, pointed out the importance of promoting health programs, especially concerning the most active people from this age, which can result in positive impacts on the quality of life related to health. Taking into consideration the aspects mentioned previously, specially the increasing number of elderly people, the Physiotherapy course of University of Franca (UNIFRAN) has created a program called Programa de Saúde da Terceira Idade – PSTI –, in order to meet this growing population and their needs. The objective of this study was to develop a comparative analysis of the Quality of life (QL) of elderly who took part on the PSTI promoted by UNIFRAN, with elderly who did not participated, according to the WHOQOL-bref and the WHOQOl-old, as well as identify in the program elements that promote health. This is an exploratory and descriptive study with a crosssectional design with a quali-quantitative approach. For this purpose, it was used a descriptive not-structured participant-observation and document analysis for the qualitative approach, besides the evaluation of 40 elderly of both genders, 20 were part of the group of participants (GP) and 20 were part of the group of nonparticipants (GNP) of the program, in which they were evaluated using the tools of WHOQOL – bref e WHOQOL – old. One may notice the increased participation of females in both groups, and most are in the GP aged 60-69 years and may be seen a resemblance to the GNP, with greater presence of women in the same age group. With the application of specific tools we can see a better perception of overall QOL (86.65 ± 7.80 X 75.95 ± 10.29) and the facets past activities, present-future (68.44 ± 12.58 X 55 , 63 ± 18.13), social participation (67.81 ± 9.35 X 52.19 ± 16.38) and death and dying (69.06 ± 23.95 X 47.19 ± 29.21) (WHOQOL -old) compared to the GNP GP. Furthermore, we observed an increase in perception of QoL in the physical (63.57 ± 11.56 X 53.39 ± 16.03) and mental (70.63 ± 9.31 X 60.62 ± 11.98) (WHOQOL-BREF) in GP compared to GNP. The results of this study showed us that there was not only one improvement in the scores: physical and psychological aspect of the elderly PSTI participant, as it was expected in the initial hypothesis. Thus, we suggest that PSTI can influence other aspects of life of its participants, because the instruments used, although they are considered generic in their assessments, suggest positive influences of the actions promoted by the program.